Thermal performance of a building envelope including microencapsulated phase change materials (PCMs): A multiscale experimental and numerical investigation - Gbekou, Franck Komi; Belloum, Rahma; Chennouf, Nawal; Agoudjil, Boudjemaa; Boudenne, Abderrahim; Benzarti, Karim (Building and environment, 2024)
This study aims to assess the thermal behavior of a cement mortar (denoted M15D) incorporating microencapsulated biobased phase change materials at both wall and building scales. A bi-climatic chamber setup was employed to subject the wall to distinct thermal conditions simulating outdoor and indoor environments, using heating and cooling solicitations. Temperature sensors, strategically positioned at various depths, allowed the monitoring of temperature within the walls during the experiments. On a building scale, the thermal performance of M15D was predicted using two mathematical models describing heat transmission in porous systems incorporating phase-change materials. Numerical simulations were carried out using COMSOL Multiphysics and EnergyPlus software. The results obtained were validated against experimental data, at the wall scale and subsequently developed to the building scale. The outcomes highlighted that the incorporation of microencapsulated biobased phase change materials significantly influences both building energy consumption and interior temperature. The heat storage capacity offered by M15D demonstrated a significant impact on thermal performance, leading to energy savings of up to 33% for heating and 31% for cooling, contingent on climate conditions. In conclusion, the integration of biobased phase change materials in the cement mortar (M15D) displays benefits in enhancing thermal performance at building scales. •Thermal behavior of cement mortar including microencapsulated biobased PCMs.•Impact of heat transfer on walls incorporating PCMs under varying thermal scenarios.•Validation of the PCM models in EnergyPlus and COMSOL Multiphysics.•Effect of PCM integration on building thermal performance in diverse climates.•PCMs efficiency depends on climate, with potential limitations in hot-dry regions.